Strategi Penulisan Artikel Jurnal Bagi Guru-Guru SMP Negeri 8 Tambang Kabupaten Kampar - Alber, Alber; Etfita, Fauzul; Febria, Rhani; Satria, Yoga (UIR Press, 2025)
The implementation of this community service started from the many complaints from teachers who had difficulty writing journal articles. This problem arises because they have not received training in writing and publishing scientific papers, so their motivation is low, and this has an impact on promotion. Apart from that, there is a lack of references and limited knowledge regarding writing articles. In fact, research activities and writing scientific articles are basic or mandatory for teachers in order to increase educational competence. Based on this, the aim of article writing training is to increase the productivity of writing scientific articles and publishing them, as well as increasing teacher professionalism and competence, increasing teacher self-confidence, and enabling teachers to actively develop their knowledge and skills. This training uses a classical and individual approach. The classical approach is carried out in two stages. First, the PKM team came to the school to conduct observations and needs analysis, then provided direct training to teachers at SMP Negeri 8 Tambang Kab. Kampar regarding writing journal articles. Second, training is carried out using lecture, tutorial, and practical methods. Meanwhile, an individual approach is taken in mentoring activities by guiding teachers in compiling and writing journal articles. The results of PKM activities related to journal article writing strategies increased understanding and motivation of teachers at SMP Negeri 8 Tambang Kab. Kampar in writing journal articles.